Evaluasi Kebijakan Penurunan Stunting di Kabupaten Kuantan Singingi - Vivin Delvya Roza; Harmelita Harmelita; Zulkarnaini Zulkarnaini (Konstitusi : Jurnal Hukum, Administrasi Publik, dan Ilmu Komunikasi, 2025)
This study analyzes the evaluation of stunting reduction policies in Kuantan Singingi Regency, Indonesia, using William N. Dunn's policy evaluation theory. Stunting is a serious nutritional problem that impacts children's growth and development, especially in the first 1000 days of life. Although there has been a decrease in stunting prevalence in Riau Province, Kuantan Singingi Regency experienced an increase in stunting rates from 17.8% in 2022 to 23% in 2023, making it the highest in the province. The evaluation was conducted based on five criteria: effectiveness, adequacy, equity, responsiveness, and accuracy. The results showed that despite significant efforts in policy implementation, the target for reducing stunting prevalence has not been achieved, with communication between officers and the community still lacking. There is a shortage of skilled personnel and funds, and unequal access to health services. The policy provides a clear framework, but information about the program is still lacking in the community. The assumptions underlying the policy are quite strong, and positive impacts are starting to be seen, but challenges such as lack of training for officers remain. Overall, despite progress, there are still many challenges that need to be addressed to achieve the goal of reducing stunting effectively.